Coronary calcium scoring for long-term mortality prediction in patients with and without a family history of coronary disease. Issue 3 (23rd December 2015) - Knapper, Joseph T; Khosa, Faisal; Blaha, Michael J; Lebeis, Taylor A; Kay, Jenna; Sandesara, Pratik B; Kelkar, Anita A; Berman, Daniel S; Quyyumi, Arshed A; Budoff, Matthew J; Min, James K; Valenti, Valentina; et al.
Abstract : Objective: Minimal data are available regarding the long-term mortality risk of subclinical atherosclerosis using coronary artery calcium (CAC) scoring among patients with a family history (FH) of coronary artery disease (CAD). The aim of the present analysis was to assess the prognostic utility of CAC scoring among cohorts of young and older patients with and without a FH of CAD. Methods: A total of 9715 consecutive asymptomatic patients, free of known CAD, underwent CAC scoring for cardiovascular risk assessment. The primary end point was all-cause mortality, with a median follow-up of 14.6 years. Unadjusted and risk-factor adjusted Cox proportional hazard modelling was employed. We calculated the area under the curve (AUC) from receiver operating characteristics analysis. Results: 15-year all-cause mortality rates ranged from 4.7% to 25.0% for FH patients and from 5.0% to 38.0% for non-FH patients with CAC scores of 0 to >400 (p<0.0001). Effect modification by age altered the mortality risk of CAC among FH patients. For patients aged > 60 years with FH of CAD, there was a significant improvement in the AUC with CAC over CAD risk factors (AUC: 0.539 vs 0.725, p<0.001). No such improvement was observed in FH patients aged <60 years (AUC: 0.636 vs 0.626, p=0.67). Conclusion: CAC effectively stratified mortality risk of patients with and without FH of CAD. However, for younger and lower-risk FH cohorts, CAC screening did not provide additive prognostic information beyond that of the traditional cardiac risk factors.